Persepsi Mahasiswa Terhadap IFRS dan Kompetensi Mahasiswa dalam Memahami dan Mengaplikasikan IFRS - Hasiholan Pulungan, Andrey (Akuntansi dan Manajemen, 2013)
Globalization, ASEAN Free Trade started in 2015, and IFRS implementation in Indonesia require universities to produce competent accounting graduates, specifically in IFRS. The purpose of this research is to analyze students’ perceptions on IFRS and their competence in IFRS. The respondents are 81 students from three private universities in Jakarta, Banten, and West Java. The students must be taking or must have taken Advance Accounting subject. The results show that students realize that IFRS is important for working as accountant and IFRS has been also integrated in their learning process in campus. However, students perceive that they do not have good competency in understanding applying IFRS. Most respondents state that they are difficult to learn IFRS due to unclear explanation from lecturer, text book in English, and lack of facilities to learn IFRS.